Professional conscience and teacher change: an investigation into Chinese teacher professionalism - Ma, Qiuru (2017)
This qualitative research studies a group of sixteen Chinese high school teachers to explore Chinese teachers’ perceptions of professionalism as well as changes in teaching. These teachers were all graduates from Master of Education (Ed.M.) programme in a Chinese university. They differed in many aspects including teaching experiences, schools they were working for, personal histories. These teachers’ work and lives were analysed based on data generated from three rounds of semi-structured interviews. Themes emerging from the interviews suggested that it was Chinese teachers’ professional conscience that had mostly affected their sense of professionalism, and there were changes both in teachers’ perceptions and actions in teaching after their graduation from Ed.M. This research contributes to a better understanding on Chinese teachers’ professional lives by identifying professional conscience as the core of Chinese teacher professionalism. The meanings of professional conscience suggest that Chinese teachers’ perceptions of professionalism share similarities to that of teachers’ in the West. The fluctuations of professional conscience through teachers’ lives has challenged stereotypes of teachers in the Chinese society.